Studies on the human gut microbiota : Relevance for maturation, inflammation and nutritional processes - Schwiertz, Andreas; Justus Liebig University Giessen (My University, 2012)
In this postdoctoral qualification thesis the effects and significance of the human microbiota and its members on the maturation, inflammation and nutritional processes in humans were investigated. In order to understand and exploit the impact of the gut microbes on human health and well-being, it is necessary to gain insight into the succession of the gut microbiota during aging.
Studien zur humanen Darmmikrobiota : Bedeutung für entwicklungs-, entzündungs- und Ernährungsprozesse
Keywords: ddc:570